Effect of feed additive "EnzActive Mix" on hematological and biochemical profiles of young piglets - Prudyus, T. (Scientific Progress & Innovations, 2023)
To determine the effect of the "EnzActive Mix" feed additive, two groups of piglets were formed at the pig farm of "Barkom" LLC on the principle of analogues: control (n=116) and experimental (n=114). The animals were kept in the same box under the same conditions.Pi glets were fed pre-starter feed in bulk form from the 5th day of life. For the experimental group, the feed additive "EnzActive Mix" ("Enzyme" LLC, Ukraine) was additionally introduced into the feed in the amount of 0.5 kg/t of finished feed. The duration of the experiment was 28 days from birth to weaning. The material for the study was the blood of animals from the control and experimental groups, which was taken from the cranial vena cava of suckling piglets on the 5th, 14th and 28th day. The blood was analyzed for hematological and biochemical parameters. The results of biochemical studies of the blood of experimental piglets obtained from sows fed with the feed additive "EnzActive Mix" indicated a significant increase in the albumin content by 47.61 % (p<0.01) on day 28 of life compared to animals in the control group. The animals of the experimental group showed more significant changes, in particular, the potassium content in the blood of piglets of 14 days of age was significantly higher by 16.50 % (p<0.05) than that of the control group. The level of inorganic phosphorus in the experimental group slightly decreased on the 14th day of piglet life, but compared to the control group it was slightly higher. According to the results of hematological studies in the blood of piglets of the experimental group, the total number of red blood cells was 6.1 % higher on day 28th of life than in the control group. Similar changes were detected in the hemoglobin content in the blood and the hemoglobin content in the erythrocyte during the entire suckling period. In the blood of piglets of 28 days of age, there was a tendency to increase these indicators by 10.33 % compared to the control group of animals. The studies have shown that the total number of leukocytes in the blood of piglets of the experimental group during the entire suckling period was characterized by a gradual increase. In addition, in piglets of 5 days of age, the number of leukocytes was significantly higher by 46.74 % (p<0.05), and an increase was observed on the 14th and 28th day by 35.81 % and 6.82 %, respectively. An increase in the live weight of piglets in the experimental group from birth to the fifth day after birth by 7.77 % was found compared to the control group. The statistically significant increase in live weight of piglets in the experimental group on the 14th day was 13.72 % (p<0.05), and on the 28th day of life 8.40 % (p<0.01), respectively. The average daily weight gain of the control and experimental groups during the study period was 210 g and 230 g, respectively, which is statistically significant by 9.53 % (p<0.01). The piglets of the experimental group consumed 1.89 % more pre-starter feed than the control group.